Excluding Orphan Drugs from the 340B Drug Discount Program: the Impact on 18 Critical Access Hospitals - Madeline Carpinelli Wallack; Todd Sorensen, PharmD (University of Minnesota Libraries Publishing, 2012)
Purpose: The 340B Drug Pricing Program is a federal program designed to reduce the amount that safety net providers spend on outpatient drugs. The Patient Protection and Affordable Health Care Act of 2010 extended eligibility for 340B to critical access hospitals (CAHs) for all drugs except those designated as "orphan." Because this policy is unprecedented, this study quantifies the gross financial impact that this exemption has on a group of CAHs. Methods: Drug spending for 2010 from 18 CAHs in Minnesota and Wisconsin are reviewed to identify the prevalence of orphan drug purchases and to calculate the price differentials between the 340B price and the hospitals' current cost. Results: The 18 CAHs' purchases of orphan drugs comprise an average of 44% of the total annual drug budgets, but only 5% of units purchased, thus representing a very high proportion of their expenditures. In the aggregate, the 18 hospitals would have saved $3.1 million ($171,000 average per hospital) had purchases of drugs with orphan designations been made at the 340B price. Because CAH claims for Medicare are reimbursed on a cost-basis, the Federal government is losing an opportunity for savings. Conclusion: The high prevalence of orphan drug use and considerable potential for cost reduction through the 340B program demonstrate the loss of benefit to the hospitals, Federal government and the states.